A systematic review of the occurrence of microplastics in compost: Understanding the abundance, sources, characteristics and ecological risk - Nasim Nourozi; Tooraj Massahi; Monireh Nouri; Maryam Mardani; Hooshyar Hossini (Results in Engineering)
Despite the environmental benefits of composting, recent studies worldwide have highlighted the emergence of microplastics (MPs) in compost, posing a potential threat to soil health. This systematic review summarizes existing research on MPs pollution in compost, emphasizing abundance, sources, characteristics, potential ecological risks, and future perspectives. 19 studies from different countries, mostly China, were included in the review. Compost types analyzed included animal manures, sewage sludge, municipal solid waste (MSW), and organic solid waste. Fibers, fragments, and films were the most common shapes, and most of these MPs were between 0.5 to 3 mm in size. Polyethylene (PE) and polypropylene (PP) are among the most frequently identified polymers. MPs abundance ranged from 0 to 2.88 × 105 items/kg, with the highest levels in chicken manure and animal/plant mixtures. Primary MPs sources were MSW, sewage sludge, animal manure and plant residues. Using the Hazard Index (H), the ecological risk assessment revealed a high risk (H > 100) for certain composts. Further research is needed to understand the long-term effects of MPs in compost on soil health and ecosystem functioning. Waste management and treatment processes need to be improved to reduce MPs pollution in compost raw materials. This review highlights the growing problem of MPs in compost and the need for targeted mitigation strategies.